2018
DOI: 10.14701/ahbps.2018.22.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the albumin-bilirubin score as a prognostic factor for early recurrence after curative hepatic resection for hepatocellular carcinoma

Abstract: Backgrounds/AimsThe albumin-bilirubin (ALBI) score has been validated as a predictor of disease-free survival and overall survival in hepatocellular carcinoma (HCC). The purpose of this study was to assess the ALBI score as a risk factor for early recurrence (ER) after curative liver resection in HCC.MethodsPatients who underwent liver resection with curative intent for HCC without previous treatment between January 2004 and December 2014 were included in this retrospective study. The utility of the ALBI score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
8
0
3
Order By: Relevance
“…The ALBI grade has been validated as a prognostic factor for OS in HCC [34]. Several studies have also reported that the ALBI grade is a feasible predictive marker for tumor recurrence in post-resection HCC [35,36]. Consistent with previous studies, ALBI grade 2 was an independent predictor of RFS in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The ALBI grade has been validated as a prognostic factor for OS in HCC [34]. Several studies have also reported that the ALBI grade is a feasible predictive marker for tumor recurrence in post-resection HCC [35,36]. Consistent with previous studies, ALBI grade 2 was an independent predictor of RFS in our study.…”
Section: Discussionsupporting
confidence: 91%
“… Lee et al. 24 Retrospective 465 Resection Preoperative ALBI grade, but not postoperative ALBI, was an independent risk factor for early recurrence (<1 year). ALBI grade was not found to be associated with late recurrence (>1 year).…”
Section: Albi Grade As a Predictor In Early-stage Hccmentioning
confidence: 98%
“…Both preoperative and postoperative ALBI grades were found to be independently associated with recurrence after surgery. [24] , [25] , [26] , [27] Two retrospective studies from Taiwan have demonstrated a more effective role of postoperative than preoperative ALBI grade in predicting late-recurrences and long-term prognosis, even years after surgery. 28 , 29 Moreover, changes in ALBI grade after hepatectomy were found to be independently associated with inferior OS and recurrence-free survival (RFS).…”
Section: Albi Grade As a Predictor In Early-stage Hccmentioning
confidence: 99%
“…Among other circulating markers or composite scores, the albuminbilirubin (ALBI) score has been validated as a predictor of survival in HCC [79] . Recently, an Asiatic study [80] evaluated the role of ALBI in predicting early recurrence. It was found that an ALBI grade ≥ 2 (P = 0.003) in addition to HBV surface antigen (HBsAg)-positive status (P < 0.001), tumor size ≥ 3.5 cm (P ≤ 0.001), lympho-vascular invasion (P = 0.001), and the presence of satellite lesions (P = 0.009) were the only predictors of early HCC recurrence on multivariate analysis.…”
Section: Circulating Biomarkersmentioning
confidence: 99%